2012
DOI: 10.3892/mmr.2015.3495
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen permease regulator-like 2 enhances sensitivity to oxaliplatin in colon cancer cells

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. Chemotherapeutic compounds used for the treatment of CRC include oxaliplatin (L-OHP). While L-OHP improves CRC survival, certain patients are resistant. The nitrogen permease regulator like-2 (NPRL2) gene is a candidate tumor suppressor gene that resides in a 120-kb homozygous deletion region on chromosome 3p21.3. In the present study, it was demonstrated that NPRL2 overexpression increases the sensitivity of HCT116 cells to L-OHP. The IC50 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Colony formation was impaired in NPRL2 ++/++ cells and this inhibition of colony formation and induction of apoptosis were significantly enhanced with the carboplatin treatment. Our group along with others in different cancers previously reported that NPRL2 enhances sensitivity to chemotherapy and overcomes drug resistance (10,11,3133). Other studies also have shown that NPRL2 promotes chemoresistance in prostate cancer by activating autophagy (34,35).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Colony formation was impaired in NPRL2 ++/++ cells and this inhibition of colony formation and induction of apoptosis were significantly enhanced with the carboplatin treatment. Our group along with others in different cancers previously reported that NPRL2 enhances sensitivity to chemotherapy and overcomes drug resistance (10,11,3133). Other studies also have shown that NPRL2 promotes chemoresistance in prostate cancer by activating autophagy (34,35).…”
Section: Discussionmentioning
confidence: 61%
“…However, we recently established the role of TUSC2, another tumor suppressor gene in the same cluster in chromosome 3p21. 31, in activating innate and adaptive immunity. TUSC2 selectively augments natural killer (NK) cells and cytotoxic T lymphocyte (CTL) activity in peripheral blood and the TME, induces a Th1-mediated immune response, and downregulates MDSC and regulatory T cells (Treg) (19).…”
Section: Introductionmentioning
confidence: 99%
“…We have explored the role of NPRL2 in drug resistance against L-OHP11 and 5-FU12 on HCT116 cells, showing that NPRL2 enhanced the sensitivity of CRC cells to L-OHP and 5-FU. In the present study, we examined the effects of NPRL2 in combination with L-OHP or 5-FU on CRC in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, NPRL2 reportedly played pro-tumor roles in prostate cancer 9. Our previous studies have revealed that NPRL2 acted as a functional tumor suppressor in the CRC cell lines HCT116 and HT29,10 enhanced the sensitivity of HCT116 cells to oxaliplatin11 and 5-fluorouracil,12 and was downregulated at both the blood and tissue levels in CRC patients compared with that in healthy individuals 13…”
Section: Introductionmentioning
confidence: 99%
“…Based on the level of DNA lesions, the stimulation of DNA damage signaling leads to DNA repair or apoptosis [ 7 ]. Evaluations have revealed that NPRL2 elevates vulnerability to anticancer drugs and apoptosis and we previously showed that NPRL2 improves sensitivity to oxaliplatin in colon cancer cells [ 5 , 8 ]. CPT-11 and oxaliplatin are the most often utilized chemotherapy treatments for CRC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%